What Makes Teachers of EFL Professional or Unprofessional - Muhammad Amin (Jurnal Pendidikan Humaniora, 2014)
Abstract: This study aimed to investigate factors attributable to English teacher professional becoming and how the factors have shaped their professionalism. The subjects of the study, called informants, were six English teachers from upper secondary level of education (Sekolah Menengah Atas (SMA) and Madrasah Aliyah (MA)) in three different regions in Indonesia: Malang, Mataram, and Lombok Barat. The research design was constructivist grounded theory. Findings of the study reveal that, prior to their teaching induction, early interests in English and high aptitude are two contributing factors. After the induction, their professional becoming is influenced by level of job satisfaction, commitment to their own and student learning, communication skills and resilience. Recommendations to obtain potential professional teachers of EFL and strategies to help them develop and maintain their professionalism are also discussed.Key Words: teacher professionalism, personal factors, environmental factors, commitment, resilience Abstrak: Penelitian ini bertujuan meneliti faktor-faktor yang berperan dalam pembentukan profesionalitas guru Bahasa Inggris dan bagaimana faktor-faktor itu membentuk profesionalisme mereka. Enam informan yang merupakan guru SekolahMenengah Atas (SMA) and Madrasah Aliyah (MA) di tiga daerah di Indonesia—Malang, Mataram dan Lombok Barat—menjadi subjek penelitian ini. Desain penelitian ini adalah teori grounded konstruktivis. Temuan penelitian ini adalah bahwa minat dan bakat yang kuat dalam Bahasa Inggris merupakan faktor yang berperan dalam pembentukan profesionalisme sebelum (seseorang) menempuh pendidikan guru. Setelah pendidikan guru ditempuh, profesionalisme dibentuk oleh tingkat kepuasan kerja, komitmen terhadap pembelajaran diri maupun siswa, keterampilan berkomunikasi dan kelenturan mengembalikan semangat (motivasi) bekerja yang turun atau hilang.Kata kunci: profesionalisme guru, faktor pribadi, faktor lingkungan, komitmen, kelenturan